2022
DOI: 10.1186/s41235-022-00438-x
|View full text |Cite
|
Sign up to set email alerts
|

Face masks affect emotion categorisation, age estimation, recognition, and gender classification from faces

Abstract: Although putting on a mask over our nose and mouth is a simple but powerful way to protect ourselves and others during a pandemic, face masks may interfere with how we perceive and recognize one another, and hence, may have far-reaching impacts on communication and social interactions. To date, it remains relatively unknown the extent to which wearing a face mask that conceals the bottom part of the face affects the extraction of different facial information. To address this question, we compared young adults’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 102 publications
3
16
0
Order By: Relevance
“…Identification accuracy and time differed between men and women. A study on female facial expression identification demonstrated that women have faster and more accurate reaction times than men ( Lewin and Herlitz, 2002 ), and also confirmed by other studies ( Megreya et al, 2011 ; Godard et al, 2013 ; Hansen et al, 2021 ; Wong and Estudillo, 2022 ). Lewin and Herlitz (2002) indicated that women’s higher face recognition performance was hypothesized to be related to either their higher verbal ability or to their superiority in recognizing female faces.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Identification accuracy and time differed between men and women. A study on female facial expression identification demonstrated that women have faster and more accurate reaction times than men ( Lewin and Herlitz, 2002 ), and also confirmed by other studies ( Megreya et al, 2011 ; Godard et al, 2013 ; Hansen et al, 2021 ; Wong and Estudillo, 2022 ). Lewin and Herlitz (2002) indicated that women’s higher face recognition performance was hypothesized to be related to either their higher verbal ability or to their superiority in recognizing female faces.…”
Section: Discussionsupporting
confidence: 71%
“…During a typical test, a serial list of unfamiliar faces was displayed for few seconds each, and participants were requested to memorize these faces, as they had to identify them from unfamiliar faces later. In such studies, women superiority in face identification was consistently represented by their higher accuracy compared to men ( Megreya et al, 2011 ; Godard et al, 2013 ; Hansen et al, 2021 ; Wong and Estudillo, 2022 ). Furthermore, Sun et al (2017) used a modified delayed matching-to-sample task to investigate the time course characteristics of face identification by event-related potential (ERP) for both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar static-based face emotion recognition task, Rinke et al ( 2022 ) showed that the impairment was largest for disgust, followed by fear, surprise, sadness, and happiness. It was not significant for anger (also see Wong & Estudillo, 2022 ) or neutral expressions. Here, they concluded that participants were likely to confuse emotions that share activation of the visible muscles in the upper half of the face.…”
mentioning
confidence: 87%
“…To this aim, in this thematic series, the detrimental effects of masks were investigated in children (Stajduhar & Freud, 2022 ) and in adults with Autistic Spectrum Disorder (Tso et al, 2022 ). Despite the detrimental effect of masks on famous face identification (Wong & Estudillo, 2022 ) familiarity-detection could still occur (Carlow et al, 2022 ). Research showed that it was harder to remember not only the identity of unfamiliar faces but whether or not that unfamiliar face wore a mask (Kollenda & de Haas, 2022 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation